Complications Related to Pectus Carinatum Correction: Lessons Learned from 15 Years' Experience. Management and Literature Review. Issue 2 (August 2016) - Del Frari, Barbara; Sigl, Stephan; Schwabegger, Anton H.
Abstract : Background: Various methods of corrective thoracoplasty for pectus carinatum deformity have been described, but to date no studies describe a review of complications and how to manage them. Complications are dependent not only on the technique used and the patient's age, but also on the experience of the treating surgeon. The authors present their 15 years' experience with surgical correction of pectus carinatum and the complications that have occurred. A literature review regarding complications with pectus carinatum surgery is performed. Methods: A retrospective review of 95 patients (mean age, 19 years) was performed. One hundred four surgical procedures for repair of pectus carinatum were performed from July of 2000 to July of 2015 using a modified Ravitch technique, bioabsorbable material, postoperative bracing, and in some cases a diced rib cartilage graft technique. Intraoperative and postoperative complications were evaluated. Results: The mean patient follow-up was 13.6 months (range, 4 months to 9.75 years). Intraoperative complications were pleura lesion and laceration of the internal mammary vein. Postoperative complications were recurrent mild protrusion, persistent protrusion of one or two costal cartilages, minor wound healing delay, skin ulcer, hypertrophic scar, transient intercostal dysesthesia, marginal pneumothorax, seroma, meningitis, and epidural hematoma. Conclusions: In our reported series of pectus carinatum repair, increasing experience and progressively less extensive techniques have resulted in fewer complications, low morbidity, and early return to activity. Complications were observed in the early period of application, predominantly because of a lack of experience, and usually subsided with increasing numbers of patients and frequency of surgery. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Coding Perspective for this Article is on Page 328e.